2016
DOI: 10.1177/0042085916656900
|View full text |Cite
|
Sign up to set email alerts
|

“Are You Gonna Take My Job Away?”: Latina Bilingual Education Teachers’ Relationships With White Colleagues in a White Racial Frame

Abstract: Using a White racial frame as a theoretical framework, this study investigated the relationship between two Latina bilingual education teachers and their White colleagues. A qualitative analysis reveals that the participants demonstrated effective teaching skills using their cultural attributes. However, the participants’ competence stirred jealousy and fear among the colleagues who displayed emotionally driven responses, such as microaggressions, and they were positioned as competitors rather than collaborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 51 publications
(53 reference statements)
1
25
1
Order By: Relevance
“…Results regarding administrative support and workload manageability contrast with prior qualitative research indicating teachers of color often experience more challenging relationships with administrators (e.g., Amos, 2020), especially White administrators (e.g., Bednar & Gicheva, 2017), and that teachers of color are often asked to fulfill time-consuming extra responsibilities for serving students of color (e.g., Achinstein & Ogawa, 2011; Bristol & Mentor, 2018). Prior qualitative research consistently indicates that teachers of color, including SETs of color, are often asked to take on additional responsibilities for serving as cultural brokers and behavior managers for students of color (e.g., Scott, 2020; Scott et al, 2021), which may lead to less manageable workloads.…”
Section: Discussioncontrasting
confidence: 96%
“…Results regarding administrative support and workload manageability contrast with prior qualitative research indicating teachers of color often experience more challenging relationships with administrators (e.g., Amos, 2020), especially White administrators (e.g., Bednar & Gicheva, 2017), and that teachers of color are often asked to fulfill time-consuming extra responsibilities for serving students of color (e.g., Achinstein & Ogawa, 2011; Bristol & Mentor, 2018). Prior qualitative research consistently indicates that teachers of color, including SETs of color, are often asked to take on additional responsibilities for serving as cultural brokers and behavior managers for students of color (e.g., Scott, 2020; Scott et al, 2021), which may lead to less manageable workloads.…”
Section: Discussioncontrasting
confidence: 96%
“…In Amos’s (2020) study, novices reported they were not provided the supports other novices received. One novice shared, “The assistance a fellow third grade teacher, a new white female who speaks Spanish, got was phenomenal.…”
Section: Resultsmentioning
confidence: 99%
“…In Amos’s (2020) study of two Mexican American female teachers, Erika explained how she had students call their parents during class to share good news with them in Spanish, explaining, “I will tell kids, ‘Go call your mom. The phone is right there.…”
Section: Resultsmentioning
confidence: 99%
“…Research continues to demonstrate how racialized spaces, working conditions, and collegial relationships affect TOC. Latina teachers reported White colleagues feeling threatened by their abilities (Amos, 2020), and noted that their White colleagues responded with “emotionally driven responses, such as microaggressions, sabotage, intentionally not helping at all, and surveillance” (p. 659). In Bristol’s (2018) study of Black male teachers, participants reported that being Black “caused people to fear them in their schools” (p. 345).…”
Section: Literature Reviewmentioning
confidence: 99%